A Review on the Sublethal Effects of Pure and Formulated Glyphosate on Bees, with a Focus on Social Bee Species - Priyanshu Pawar; Mounika Jarpla; D. K. Narwade; Samreen; Rajan ghanghas; Satyabrata Sarangi; Vasanthan E; Rajkumari (Archives of Current Research International, 2024)
Glyphosate, one of the most widely used herbicides globally, has been extensively applied in agriculture due to its efficacy in weed control. However, recent studies have raised concerns about its sublethal effects on non-target organisms, particularly social bee species such as honeybees (Apis mellifera), bumblebees (Bombus spp.), and stingless bees (e.g., Melipona, Trigona). While glyphosate’s primary mechanism targets the shikimate pathway, which is absent in animals, emerging evidence suggests it can indirectly impact bees by altering their gut microbiota, immune responses, and behavior. Research shows that even at sublethal doses, glyphosate can impair navigation, learning, and foraging efficiency, leading to reduced colony growth and survival rates. Field and laboratory studies indicate that the impact is exacerbated when bees are exposed to formulated products containing surfactants, which increase glyphosate’s toxicity. Furthermore, the disruption of social behaviors within colonies, such as communication through the waggle dance in honeybees, has profound implications for hive health and productivity. Despite growing evidence, there remain significant gaps in our understanding of glyphosate’s long-term and chronic effects, especially across diverse ecosystems and bee species. Current research is limited by a lack of longitudinal field studies that assess the cumulative impact of low-dose exposure over multiple generations. Most studies have focused on honeybees, with less attention given to wild and native bee populations, which may respond differently to glyphosate. To address these challenges, future research must prioritize mechanistic studies, explore eco-friendly alternatives to glyphosate, and implement integrated pest management strategies to reduce agrochemical dependence. Collaboration among scientists, policymakers, and stakeholders is critical to developing evidence-based regulations that protect pollinator health. Given the essential role bees play in global food security through pollination, protecting these vital species from the sublethal effects of glyphosate is not only an ecological imperative but also a socioeconomic necessity. Immediate actions in research, policy reform, and sustainable agricultural practices are needed to mitigate the risks posed by glyphosate and safeguard the future of pollinators.